Importance of Cash Flow Statement in Transition to International Standards of Financial Reporting - Alijonovich, Murodov Fakhriddin; Akhmadjonovich, Nazarov Akmaljon (Central Asian Journal of Innovations on Tourism Management and Finance, 2022)
this article discusses the importance and development of the cash flow statement in the context of the transition to international standards of financial reporting, as well as the improvement of the form of the current report in our republic. It is recognized that cash flows are one of the first indicators that allow identifying potential problems and economic risks of a company, and that the main source of this information is the cash flow statement.